CURRENT TRENDS IN ANTIBIOGRAM WITH SPECIAL REFERENCE TO ANTIBIOTIC STEWARDSHIP FOR CASES OF NEONATAL SEPSIS AND CORRELATION WITH PROCALCITONIN AND INTERLEUKIN-6 AS DIAGNOSTIC MARKERS AT NEONATAL INTENSIVE CARE UNIT, MEDICAL COLLEGE, KOLKATA - SUBHRANIL MAL; BIYANKA SAU; DIBYENDU RAY CHAUDHURI; BIRUPAKSHA BISWAS; SUHENA SARKAR (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: The objectives of this study were to assess current trends in the microbiological profile and antibiotic resistance in neonatal sepsis, with emphasis on the diagnostic utility of procalcitonin (PCT) and interleukin-6 (IL-6) as early markers. Methods: Blood samples were collected from neonates with suspected sepsis for microbial culture, antibiotic susceptibility testing, and quantitative estimation of PCT and IL-6. Clinical correlation was established to assess the utility of these biomarkers in early diagnosis and prognosis. Results: The most frequently isolated pathogens included Klebsiella pneumonia (16%), Acinetobacter baumannii complex (15%) and coagulase-negative staphylococci (11%), with significant resistance to commonly used antibiotics. PCT and IL-6 levels were elevated in cases with clinical symptoms, suggested by their p-values. IL-6 showed strong associations with respiratory distress, bronchial breathing, and abnormal chest X-rays (**p<0.01), whereas PCT was significant for bronchial breathing and chest X-ray findings (*p<0.05). A positive correlation between elevated biomarker levels and radiological or clinical findings reinforced their diagnostic importance. Conclusion: PCT and IL-6 serve as valuable adjuncts in the early diagnosis and monitoring of neonatal sepsis. The research asserts the need of combining biomarker-based diagnostics with antibiotic stewardship to combat antimicrobial resistance and improve clinical outcomes in neonates.